2020
DOI: 10.1007/s11748-020-01428-w
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis comparing transaxillary and transaortic transcatheter aortic valve replacement

Abstract: Background The alternative access route of choice for transcatheter aortic valve replacement (TAVR) remains to be elucidated due to lack of evidences. We performed a meta-analysis comparing the outcomes of two common alternative access routes, transaxillary (TAx) and transaortic (TAo) approaches. Methods The PubMed/MEDLINE, Embase, and Cochrane library from inception to December 2018 were searched to identify the articles reporting data on both TAx-TAVR and TAo-TAVR. Patients' baseline characteristics, procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…In contrast, the most recent studies of other nontransfemoral approaches in usual TAVR populations using the most recently developed valves with very fine delivery systems, such as SAPIEN 3 and SAPIEN 3 Ultra , have shown mortality rates ranging between 4.3% and 5.2%, and stroke rates between 4.2% and 7.4% 13 . Even though our cohort does not necessarily reflect the broader population of patients who cannot undergo other non‐TF approaches, the interventional risk with other nontransfemoral approaches in patients with diverse AP remains high, as recent studies have reported considerably high rates of vascular injuries (between 4.8% and 6.9%) 14 . Lastly, the invasiveness of a procedure depends not only on whether it has been performed percutaneously.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In contrast, the most recent studies of other nontransfemoral approaches in usual TAVR populations using the most recently developed valves with very fine delivery systems, such as SAPIEN 3 and SAPIEN 3 Ultra , have shown mortality rates ranging between 4.3% and 5.2%, and stroke rates between 4.2% and 7.4% 13 . Even though our cohort does not necessarily reflect the broader population of patients who cannot undergo other non‐TF approaches, the interventional risk with other nontransfemoral approaches in patients with diverse AP remains high, as recent studies have reported considerably high rates of vascular injuries (between 4.8% and 6.9%) 14 . Lastly, the invasiveness of a procedure depends not only on whether it has been performed percutaneously.…”
Section: Discussionmentioning
confidence: 86%
“…13 Even though our cohort does not necessarily reflect the broader population of patients who cannot undergo other non-TF approaches, the interventional risk with other nontransfemoral approaches in patients with diverse AP remains high, as recent studies have reported considerably high rates of vascular injuries (between 4.8% and 6.9%). 14 Lastly, the invasiveness of a procedure depends not only on whether it has been performed percutaneously. The TA approach represents an aorta no-touch technique and hence should be considered as the most minimally invasive technique for TAVR in patients with diverse AP for as long as evidence on other approaches is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported considerably high rates of vascular injuries (4.8%-6.9%). 13 Interestingly, in the vast majority of the abovementioned studies, no contraindications of the respective approaches (TS, Tax, and TC) have been reported, and the contraindications for these approaches have been poorly studied. This may be one of the reasons why the results of these approaches have not yet matured.…”
Section: Discussionmentioning
confidence: 99%
“…Purse-string suture and cannulation of the ascending aorta are standard procedures and are performed daily. Therefore, access site complications are not common in the literature and are described are described in 2 to 5% only (17,(22)(23)(24). The TAo access is of particular importance in case of contraindications for TF TAVI and concomitant calcifications of the supra-aortic branches and the aortic arch since under these circumstances other alternative access routes, such as TAx or TC, are not feasible (25).…”
Section: Preprocedural Planning: Indications For Tao Accessmentioning
confidence: 99%
“…Other alternative access (AA) routes, such as transaxillary (TAx) and transcarotid (TC), offer comparable advantages over TA. Several studies have compared these procedures with contrary results in terms of procedural success, perioperative outcome, and mortality (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%